Diversifikasi Produk Budidaya Larva Lalat Tentara Hitam Di CV Ahasa Larva Group Samarinda, Kalimantan Timur - Nugroho, Rudy Agung; Subagyono, Dirgarini Nurlianti Julia; Sanjaya, Ari Susandy; Arianto, Reza Fahyuzi; Syaharani, Ramada; Kurniawan, Fandy Ahmad; Rudianto, Rudianto (Universitas Pahlawan Tuanku Tambusai, 2025)
The Black Soldier Fly larvae (Hermetia illucens L.) are widely cultivated for organic waste bioconversion. However, overproduction and inefficient cultivation methods have created challenges for CV Ahasa Larva Group in Samarinda, East Kalimantan. This community service program aimed to provide technical assistance on maggot farming using magoboxes, the production of maggot substrates from fermented palm kernel cake, and the development of maggot-based products such as oil and biodiesel. The activities included preparation, implementation, and evaluation through theoretical presentations, discussions, and practical training. The ten participating maggot farmers successfully adopted new cultivation techniques and product diversification methods. The evaluation revealed a 75% increase in knowledge and understanding regarding maggot cultivation and the production of derivative products. This initiative contributes to the sustainable development of maggot farming, enhances product value, and supports local economic growth..